PP.39.23: THE ROLE OF ANGIOTENSIN II AT1 RECEPTOR IN THE ALDOSTERONE PROTHROMBOTIC ACTION. (June 2015) - Gromotowicz-Poplawska, A.; Kramkowski, K.; Stankiewicz, A.; Strzyz, M.; Gredzinski, T.; Szemraj, J.; Chabielska, E.
Abstract : Objective: We showed previously that acute aldosterone (ALDO) infusion resulted in impairment of the fibrinolytic process and activation of coagulation cascade, consequently leading to augmentation of stasis-induced venous thrombosis in rats. This prothrombotic effect of ALDO was only partially mediated by the mineralocorticoid receptor (MR). Bearing in mind that ALDO potentiates the angiotensin II (Ang II) effects, in the present study we investigated the role of Ang II in the mechanism of ALDO prothrombotic action. Design and method: Male Wistar rats (300–350 g, n = 8–12) were used in this study. Aldosterone (ALDO, 30 μg/kg/h) or 0, 4% ethanol (VEH; 2 ml/kg/h) was infused into the femoral vein 5 minutes before the induction of venous thrombosis and was continued for 1 h. Valsartan (VAL, 10 mg/kg), AT1 antagonist, was injected as a bolus into femoral vein 5 minutes before ALDO infusion. Venous thrombosis was performed by the vena cava ligation. The formed thrombus was removed and weighted after 24 h. Plasminogen activator inhibitor (PAI-I), tissue plasminogen activator (t-PA), thrombin activatable fibrinolysis inhibitor (TAFI) plasma levels were measured by ELISA. Results: We observed that one-hour infusion of ALDO resulted in a significant increase in venous thrombus weight (p < 0.01) and markedly elevated incidence of venous thrombosis, paralleled by significant increase in PAI-1 (p < 0.001) and TAFI (p < 0.001) as well as decrease in t-PA (p < 0.001) plasma levels in comparison to VEH. VAL administered together with ALDO reduced thrombus formation (p < 0.05) and diminished the incidences of thrombosis. We also observed that pretreatment with VAL reversed slightly the ALDO-induced decrease in t-PA level and reduced significantly TAFI (p < 0.05) and PAI-1 plasma levels (p < 0.05, vs ALDO). Conclusions: This study provides evidence that prothrombotic effect of ALDO is also mediated by the angiotensin II AT1 receptor. The mechanism of ALDO-induced AT1 activation involved impairment of the fibrinolytic process. The present study supplies our knowledge about the multiple mechanism of ALDO prothrombotic action, which is mediated via MR and AT1 receptors.